Perimesencephalic Hemorrhage: A Review of Epidemiology, Risk Factors, Presumed Cause, Clinical Course, and Outcome. Issue 6 (June 2018) - Mensing, Liselore A.; Vergouwen, Mervyn D.I.; Laban, Kamil G.; Ruigrok, Ynte M.; Velthuis, Birgitta K.; Algra, Ale; Rinkel, Gabriel J.E.
Abstract : Background and Purpose—: We systematically reviewed the literature on epidemiology, risk factors, presumed cause, clinical course, and outcome of perimesencephalic hemorrhage. Methods—: PubMed, Embase, and the Cochrane Library were searched until March 2016. Quality assessment was done by 2 authors independently. Pooled prevalence ratios and pooled odds ratios with 95% confidence intervals were calculated for data extracted from case–control studies. Results—: We included 208 papers. The incidence of perimesencephalic hemorrhage is ≈0.5 per 100.000 person-years, men are more often affected, and no risk factors were confirmed. Two decision analyses both found that a single, high-quality computed tomography angiography is the preferred diagnostic approach. Short-term complications, such as hydrocephalus or cranial nerve palsies, are rare, and usually transient, with the exception of acute symptomatic hydrocephalus necessitating treatment in 3% of patients. Lacunar infarcts in the brain stem were convincingly described in 4 patients only. Fatal rebleeding after installment of anticoagulation in the initial days after the hemorrhage was described in 1 patient. At long-term follow-up, death related to the hemorrhage has not been reported, disability is found in 0% to 6%, and neuropsychological sequelae are suggested. Conclusions—: A single, high-quality computed tomography angiography is the preferred diagnostic strategy. Short-term complications are rare and often transient. Long-term outcome is excellent with respect to disability and death, but high-quality studies focused at neuropsychological sequelae are needed. Abstract : Supplemental Digital Content is available in the text.